PENERAPAN KONSEP DAN PRlNSIP PEMBELAJARAN KONTEKSTUAL (CONTEXTUAL TEACHING AND LEARNING) DAN DESAIN PESAN DALAM PENGEMBANGAN PEMBELAJARAN DAN BAHAN AJAR - Abdul Gafur (Jurnal Cakrawala Pendidikan, 2003)
In designing, developing, and delivering instructional materials, both for face to face apd written or mediated instruction there are some important principles that should be considered. Among the principles are the contextual teaching and learning (CTL) and the instructional message design principles. The contextual teaching and learning principles consists of relating, experiencing, aplying, cooperating, and transferring. The instructional message design principles consists ofreadiness and motivation, attention directing devices, repetition, student's active participation, and feedback. To get effective instruction, those principles should be imple mented and integrated to the instructional strategy components whichconsists ofpre instructional activities, presenting information, eliciting performance, providing feedback, testing, and follow up activities (transferring, remedial, and enrichment). Key words: Contextual teaching and learning, instructional message design, instructional strategy components.